Semiologic analysis of light in Luces de Bohemia (1924) - Castrillo Salvador, Violeta (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
Luces de bohemia (1924) is, in all probability, the most famous of Valle-Inclan's plays and, maybe, one of the most commented. Nevertheless, it is always possible to try a new interpretation, thanks to the high quality of the play. In this paper, I propose a new one, based on the "esoteric" knowledge of the writer and the symbolic value that Light holds in Theosophy: Ligh as Truth on the Platonic game throug the Myth of the Cavern and Light as Sign both in lhe performance and in the literary text. This bright axis reveals a new structural analysis and a new  pragmatic proposal for its performance.
Keywords: Ramón María del Valle-Inclán; semiology; light